Singlehood Phenomenon : Understanding Professional Malay Muslim Women Who Have Not Married - Jamayah, Saili; Abdul Rahman, Saili (2012)
Islam permeates every facet of Malay life in the realm of values and behaviour. Changes in marital trends and family life in Malaysia and other South East Asian countries do not mirror those that have occurred in the West. Much of the research on single women in the West has only looked at singles based on their ‘civil status’ and failed to distinguish between single women who have never married and women who are divorced, widowed, separated or cohabitating. Drawing on in-depth interviews with 20 professional Malay Muslim women who have not married in Kuching, Sarawak, this research examines perspectives of these professional Malay women on being single and how singleness is interpreted among them. Although higher education, financial stability and career advancement are important for every woman, the research demonstrates that the pattern of their perspectives on marriage is consistent. The women did not vary significantly with respect to their belief in predestination regarding marriage and they hold to Qada (decree) and Qadar (destined), the fifth of the six fundamentals of Iman (faith) among Muslims. The words Qada and Qadar is a very broad concept; it brings the same meaning to some of the metaphorical statements given by the participants, such as: "Things happened for reasons”, “Blessing in disguise”, “Wisdom behind it”, “kun faya kun” (what will be will be). In the presentation, the intent is not to analyze the reasons for the growing rates of single Malay women in Malaysia; but to comprehend some explanations based on the women’s experience to the question: “why are they single?” and set out to understand “what went wrong?” It is apparent that although they enjoy their personal freedom, being single is not a personal choice. Rather, they believe in the concept of Jodoh (soul-mate as fated by God). This paper thus highlights how the Malay Muslim women vary significantly with respect to their decision in remaining single or to marry due to cultural expectations and religious values.